Mechanical Review of Fine Sand-Clay Varians - Muhammad Shalahuddin; Andre Novan; Safridatul 'Audah; Azhari; Gussyafri; Sri Djuniaty (Jurnal Inotera, 2023)
Clay in nature consist of a mixture of grains and minerals with or without the content of organic matter. The variation in the size of clay grains and the proportion of their distribution is a very useful indicator for knowing soil behavior. Testing the combination of fine sand - clay (FSC) using clay from Kulim Pekanbaru and fine sand from Teratak Buluh Riau. Variants of the percentage of FSC are carried out with the types of tests carried out are Standard Proctor Test, Unconfined Compressive strength test, Direct Shear Test and sieve analysis test and hydrometer. Increasing the percentage of clay in the FSC variant, increases the liquid limit, increasses the plastic limit and increases the plasticity index. Increases optimum moisture content, decreases maximum dry density and increases soil friction angle and decreases compressive strength